The macular microvascular changes in children with a history of retinopathy of prematurity treated with intravitreal Bevacizumab injection using optical coherence tomography angiography: a retrospective cohort - Amir Eftekhari Milani; Mohammad Hosein Ahoor; Fatemeh Etemad; Banafsheh Kharrazi Ghadim; Amin Arasteh (BMC Ophthalmology)
Abstract Objective Our study aims to evaluate and compare the macular microvascular condition of the intravitreal Bevacizumab (IVB)-treated retinopathy of prematurity (ROP) cases to the preterm cases without ROP and spontaneously regressed ROPs. Methods It is a retrospective cohort of 50 premature neonates visited from 2016 to 2017 for ROP screening in Nikookari Eye Hospital and recalled for re-evaluation in 2022. These patients were classified into three groups based on their medical documents: 1. Preterm cases without ROP (PT), 2. Spontaneously regressed ROPs (SR), and 3. IVB-treated ROPs (IVB). All the included cases underwent a thorough ophthalmic exam, cyclo-refraction, Best-corrected visual acuity (BCVA) assessment, and macular optical coherence tomography angiography (OCTA). The foveal thickness, foveal avascular zone (FAZ) area, foveal, parafoveal, and perifoveal vascular density (VD) were evaluated as the quantitative variables. Results Twenty-five male and 25 female cases with a median age of 5.0 entered the study. Twenty-six eyes were evaluated in the PT group, 50 in the SR group, and 24 in the IVB group. The SR group consisted of 25 zone-2 and 25 zone-3 ROPs. In comparison, the IVB group consisted of 9 zone-1 and 15 zone-2 ROPs (p: < 001). Also, zone-2 cases were more advanced in the IVB group. The IVB-treated eyes demonstrated a significantly higher foveal superficial capillary plexus (SCP) VD than the others (28.5% vs. 23.1 and 22.9, respectively, in PT and SR, p:0.008). However, the parafoveal deep capillary plexus (DCP) VD was lower than the PT cases (48.5% vs. 53.4, p:0.034). The FAZ area was also smaller than the PT cases (0.113 vs.0.219 mm2, p:0.032). The FAZ area was significantly positively correlated with the foveal SCP and DCP VD and negatively correlated with parafoveal DCP VD (CC: -0.770, -0.719, 0.377, respectively, p: < 0.001). Conclusion In the long term, although the IVB-treated ROP cases experience an excellent visual outcome comparable to those without ROP, they may show some macular microvascular changes. These changes might be related to the effect of IVB or the nature of more advanced stages of ROP. Graphical Abstract